Acute chorioamnionitis, histopathologic changes of the placenta and prevalence of microbial invasion in patients with preterm delivery – Review of literature - Kochoski, Goran; Spasova, Rosa; Kjaev, Ivo; Karadzova, Dafina; Stojoska Lazarova, Aleksandra; Janevska, Vesna; Spasevska, Liljana (Macedonian Association of Anatomists and Morphologists, 2019)
Aim: To review to date published results on the topic of histopathological changes of the placenta, umbilical cord and fetal membranes in patients with preterm delivery and evaluate their association with microbial invasion of the amniotic cavity and placental disc. Materials and methods: The PubMed index was searched to identify relevant articles, studies and abstracts published in English in the past 20 years (1995-2015). The following keywords were used: placenta, placental pathology, chorionamnionitis, amnionitis, funisitis, pPROM (Preterm Premature Rupture of the Membranes), intra amniotic infection and intra amniotic inflammation. Results: The results of the reviewed studies show that histopathologic changes classified as chorioamnionitis, deciduitis, vilitis and funisitis, can be present even in settings that lack clinical expression of the syndrome, such as high temperature, tachycardia and leukocytosis. The presence and intensity of the inflammatory changes are inversely proportional to the gestational age. These findings are more often present in cases of extreme rather than in cases of moderate to lateprematurity (94.4% in deliveries between 21-24 g.w contrary to 10.7% in deliveries at 33-36 g.w). At the same time, the detection rate of microbial invasion of the amniotic cavity varies in wide range from 7.4-74%, depending on the method used for sample collection (microbiological smear, amniotic fluid culture or PCR). Conclusion: Histological verification of chorioamnionitis is far more often than the clinical manifestation of the syndrome in patients with preterm labor. Considering the discrepancy between pathohistological findings and detection rate of microorganisms ethologically associated with placental inflammatory changes, the necessity for development of more sensitive techniques for microbial detection has to be prioritized.
Keywords: placenta; placental pathology; chorioamnionitis; amnionitis; funisitis; PROM; intra amniotic infection; intra amniotic inflammation